The PR power of fessing up - Soule, Sarah Anne, 1967-; Li, Lambert Zixin (MIT Sloan Management Review, 2023)
Organizations' corporate social responsibility efforts are facing closer scrutiny today than ever before. In recent years, a new reputation management strategy has emerged: the confession. The authors describe a study in which companies that confessed their inadequacy in confronting racial inequity were rated as more socially responsible than organizations that did not issue such statements. Thus, a proactive approach can be more effective than a reactive strategy for building stakeholder trust.